Pembelajaran Bahasa Arab Melalui Channel Youtube Arab Podcast - Ida Alinda Fathonah; Abdul Majid; Chairani Astina (Pusat Riset dan Inovasi Nasional, 2024)
In this modern era, technology plays a crucial role in facilitating learning and enhancing understanding of academic material. This study focuses on Arabic language learning through the YouTube channel Arab Podcast, particularly on the video content of the book